Kesadaran Masyarkat Pedagang Ikan dan Ayam Terhadap Pasar Sehat Ramah Lingkungan: Implementasi Perda Kukar No 6 Tahun 2012 - Maryah, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Entry into Regulation of Kukar Regions no. 6/2012 On Structuring and Fostering of Traditional Markets, Shopping Centers and Modern Stores in Barengi with the establishment of new market Mangkurawang. Where the market is a market that is made to meet the standards of environmentally friendly green market, thus this market also has waste management that meets the environmentally friendly standards as regulated in Law Number. 32 of 2009 Environmental Law Protection and Management. Through the sociological juridical approach, the study found that the implementation of Perda No.6 / 2012 was not maximized because of the lack of awareness of the local community about the purpose and purpose of the old market shift allocated to Pasar Baru Mangkurawang, besides the lack of supervision from Satpol PP to curb the market arrangement of the foot trader five and the lack of counseling socialization of local regulations through the extension of the hand of the market agency through the district and local kelurahan, thus the Implementation of Perda can not be realized maximally.